88.6k views
3 votes
How do you factorize p2 + 2p - 3 =0

User MyOwnWay
by
4.8k points

1 Answer

4 votes

Answer:

Solution

p = {-3, 1}

Explanation:

Simplifying

p2 + 2p + -3 = 0

Reorder the terms:

-3 + 2p + p2 = 0

Solving

-3 + 2p + p2 = 0

Solving for variable 'p'.

Factor a trinomial.

(-3 + -1p)(1 + -1p) = 0

Subproblem 1

Set the factor '(-3 + -1p)' equal to zero and attempt to solve:

Simplifying

-3 + -1p = 0

Solving

-3 + -1p = 0

Move all terms containing p to the left, all other terms to the right.

Add '3' to each side of the equation.

-3 + 3 + -1p = 0 + 3

Combine like terms: -3 + 3 = 0

0 + -1p = 0 + 3

-1p = 0 + 3

Combine like terms: 0 + 3 = 3

-1p = 3

Divide each side by '-1'.

p = -3

Simplifying

p = -3

Subproblem 2

Set the factor '(1 + -1p)' equal to zero and attempt to solve:

Simplifying

1 + -1p = 0

Solving

1 + -1p = 0

Move all terms containing p to the left, all other terms to the right.

Add '-1' to each side of the equation.

1 + -1 + -1p = 0 + -1

Combine like terms: 1 + -1 = 0

0 + -1p = 0 + -1

-1p = 0 + -1

Combine like terms: 0 + -1 = -1

-1p = -1

Divide each side by '-1'.

p = 1

Simplifying

p = 1

Solution

p = {-3, 1}

User Daniel Watrous
by
4.7k points